Performing Authenticity And Contesting Heritage In The UNESCO-Inscribed Jerusarema/Mbende Dance Of Zimbabwe - Nesta Nyaradzo Mapira; Made Mantle Hood (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
In African societies, traditional dances form and shape a multitude of cultural expressions that reflect socio-cultural status, stalwart traditions and degrees of heritage maintenance. Due to colonisation, westernisation and Christianity, the performative aesthetics of many African traditional dances have been drastically modified over time. One such traditional dance in Zimbabwe that has undergone continual socio-cultural and aesthetic change is Jerusarema/Mbende from the Murehwa and Uzumba-Maramba-Pfungwe districts of Mashonaland Eastern province. In 2005, The Mbende Jerusarema Dance of Zimbabwe was proclaimed on the United Nations Educational Scientific and Cultural Organisation (UNESCO) list of Masterpieces of Oral and Intangible Heritage of Humanity. Authentic elements of the dance were compiled by the Zimbabwe National Oral and Intangible Cultural Heritage (ZNOICH) committee in an effort to safeguard it against change. This safeguarding led the Jerusarema/Mbende dance along a contested path of endorsement and utilisation in multiple contexts by some performance ensembles such as Swerengoma, Ngomadzepasi, Zevezeve, Shingirirai and Makarekare as promoted by prominent dance festivals. These ensembles assert different agendas through music, props, instruments and dance movements. Drawing upon documentary video evidence from the National Arts Council of Zimbabwe and interviews, this paper evaluates the extent to which the authentic elements of the Jerusarema/Mbende dance inscribed on the UNESCO list have been safeguarded in formalised performances from 2013 to 2015. Video recordings from this period showing continuous participation of Ngoma Dzepasi, Makarekare and Shingirirai are used to assess similarities and differences from the fixity of authentic elements. We argue that UNESCO’s recognition of the Jerusarema/Mbende dance as intangible cultural heritage has, on the one hand, revived and maintained some characteristics of this dance but, on the other hand, gradually compromised innovative aesthetic music and dance elements introduced by inheriting generations.